Innovative Multimedia Filtration for Effective Microplastic Removal in Mangrove Ecosystems: A Sustainable Approach to Environmental Health - Wiyarno, Yoso; Widyastuti, Sri; Al Kholif, Muhammad; Gunawan, Wawan (Tecno Scientifica Publishing, 2025)
Microplastic contamination posed a significant threat to mangrove ecosystems, impacting biodiversity and water quality. This study evaluated the effectiveness of a multimedia filtration system using silica sand, zeolite, activated carbon, blood clam shells, and gravel in reducing microplastic levels in mangrove waters. Water samples were collected from the Wonorejo Mangrove Ecotourism in Surabaya, Indonesia, and were treated using two filtration reactors: Reactor 1 with sand media and Reactor 2 with clamshell media. The downward-flow filtration system demonstrated promising results, with Reactor 1 achieving a 54-60% microplastic removal efficiency and Reactor 2 showing superior performance with a 61-65% efficiency. Fiber-type microplastics were most effectively removed, with Reactor 2 achieving a 67% reduction. The findings highlighted the potential of clamshell media in enhancing filtration efficiency and promoting environmental sustainability. While the system offered a viable solution for mitigating microplastic pollution in aquatic environments, challenges such as scalability, cost-effectiveness, and long-term maintenance required further research. Future studies should focus on optimizing filtration media and assessing real-world applicability for broader environmental conservation efforts.